2017
DOI: 10.3390/min7070113
|View full text |Cite
|
Sign up to set email alerts
|

The Activation Mechanism of Bi3+ Ions to Rutile Flotation in a Strong Acidic Environment

Abstract: Lead hydroxyl compounds are known as rutile flotation of the traditional activated component, but the optimum pH range for flotation is 2-3 using styryl phosphoric acid (SPA) as collector, without lead hydroxyl compounds in slurry solution. In this study, Bi 3+ ions as a novel activator was investigated. The results revealed that the presence of Bi 3+ ions increased the surface potential, due to the specific adsorption of hydroxyl compounds, which greatly increases the adsorption capacity of SPA on the rutile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 32 publications
2
15
0
Order By: Relevance
“…In Figure 1, it can be found that the contact angle of the rutile surface was 37.6 • ± 1.5 • in the natural condition, suggesting that the natural hydrophobicity of rutile surface was very poor. This is in agreement with the results reported in previous studies [9,12]. After SPA adsorption on the un-activated rutile surface, the contact angle of the rutile surface only increased from 37.6 • to 48.7 • ± 2.0 • , which indicated that it was very difficult for SPA to be adsorbed on the un-activated rutile surface.…”
Section: Contact Angle Measurementssupporting
confidence: 93%
See 2 more Smart Citations
“…In Figure 1, it can be found that the contact angle of the rutile surface was 37.6 • ± 1.5 • in the natural condition, suggesting that the natural hydrophobicity of rutile surface was very poor. This is in agreement with the results reported in previous studies [9,12]. After SPA adsorption on the un-activated rutile surface, the contact angle of the rutile surface only increased from 37.6 • to 48.7 • ± 2.0 • , which indicated that it was very difficult for SPA to be adsorbed on the un-activated rutile surface.…”
Section: Contact Angle Measurementssupporting
confidence: 93%
“…On the basis of these previous studies, we found that the activation mechanisms of metal ions for mineral flotation were indirectly deduced by some measures, such as XPS, zeta potential, FTIR and simulation calculation [5,6,[8][9][10][11][12][13]. However, at the micro level, there was no intuitive evidence for the explanation of the activation mechanisms of Pb 2+ ions for rutile flotation.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Compared with ilmenite, the titanium in rutile is relatively easy to utilize, with a natural advantage in quality. Therefore, many studies have begun to focus on rutile beneficiation [7][8][9][10]. The majority of rutile ores are refractory ores, the concentration of which is very difficult to gauge due to the fine grain sizes associated with the gangues, the complexity of the mineralogy, and the brittleness leading to it being easily over-ground [11].…”
Section: Introductionmentioning
confidence: 99%
“…The adsorption of metallic ions on the mineral surface would lead to the variation in the zeta potential of mineral surface and alter the isoelectric point (IEP) [23][24][25][26][27][28][29]. The adsorption of cationic or anionic collectors has similar effects [30][31][32][33].…”
Section: Zeta Potential Measurementsmentioning
confidence: 99%